Peningkatan Pemahaman Guru Sekolah Indonesia Davao tentang Proyek Penguatan Profil Pelajar Pancasila Melalui Pendampingan Pembelajaran Terstruktur - Irvan, Moh. Farizqo; Sari, Elok Fariha; Ahmadi, Farid; Nugrahani, Arshanda Gusti; Zulfana, Shinta Aulidafitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This community service aims to increase the understanding of Indonesian Davao School Teachers (SID) in the Philippines regarding the Strengthening Pancasila Student Profile Project (P5). Through an In House Training approach based on structured learning, this activity succeeded in increasing teachers' understanding of P5 implementation. The mentoring activities were attended by 20 teachers at SID from elementary, junior and senior high school levels. The results of the mentoring show that there is an increase in teacher understanding regarding the implementation of P5 in the Kurikulum Merdeka. This is shown by the increase in the results of the teacher pre-test and post-test at SID amounting to 25.33 with an n-gain of 0.39 in the medium category. This activity also identified the need for more specific and focused training to support the optimization of the implementation of the Kurikulum Merdeka. As a follow-up, this service will be directed at developing advanced training modules and providing project-based assessment assistance. In addition, collaboration with various parties will be strengthened to ensure program sustainability and improve the quality of learning that is more inclusive and meaningful. This activity is a strategic step in supporting the transformation of Indonesian school education abroad.